(untitled) (Asian Business Research, 2022)
This paper empirically investigates the relationship between consumption structure, industrial structure and economic growth in Jinan City using vector autoregressive (VAR) model using 30 years of data from 1990-2020 in Jinan City. The results show that there is a two-way causal relationship between industrial structure and economic growth, and a two-way causal relationship between consumption structure and economic growth in Jinan City. Consumption structure can promote the optimization of industrial structure and further promote economic growth, while industrial structure does not play a proper role in promoting the regulation of consumption structure.